Measuring office productivity - T. McDonald; D. W. Conrath (South African Journal of Business Management, 1989)
Many organizations today are caught in the grip of a severe productivity crisis. If there is an urgent need to improve office productivity, there is also a need to be able to measure productivity in a suitable way. All the measures of total office productivity that have been found in the literature, either do not say how to measure the qualitative aspects of the output or how the quantitative and qualitative aspects are to be combined. In this paper a measure is proposed that considers both the effectiveness (quality and timeliness) and efficiency aspects of office output. An overall composite productivity index is provided. We feel that the proposed measure is an advance over current methods of measuring office productivity.
Keywords: 650